Distribuição de partículas e retenção de água em solos arenosos do estado de Mato Grosso - Torres, Gilmar Nunes (2017)
Sandy soils are part of an extensive area in the state of Mato Grosso and Brazil, although they are in the same soil class, they present different characteristics, such as the particle size distribution of the sand fraction, which allows the differentiation in characteristics such as hydraulic conductivity and water retention characteristic curve. There is a need for improvement in how the differentiation is carried out, and to find solutions that improve the physical-hydro characteristics of these soils. The objective of this work was to evaluate the retention of water in soils of different source materials, as well as the factors related to this water retention that can be used in the differentiation of these soils and in the improvement of water retention. The study areas belong to the geomorphological units of the Plateau of the Parecis, Plateau of Tapirapuã, high Depression Paraguay River and Plateau dos Guimarães. The equipment used was the analysis of the particle size distribution by laser diffraction Horiba LA-950. The methodologies tested were: laser diffraction with 20 ml NaOH, laser diffraction with 20 ml NaOH and 5 minutes of agitation with ultrasound, laser diffraction with 20 ml NaOH and 10 minutes of agitation with ultrasound, sifting (0.053 – 2.0 mm) and laser diffraction, sifting, being evaluated the fine sand fractions (0.053 – 0.25 mm), medium sand (0.25 – 0.5 mm) and coarse sand (0.5-2.0 mm), centrifuge method and pipette method. The analysis of soil particle size curves was performed by means, skewness, kurtosis and sorting according to the grain size parameters established by Folk and Ward (1957). The study compared the soil water retention capacity of different source materials through the water retention curves in the soil, which were adjusted by the model of Van Genuchten. Water retention capacity was studied in sandy soils with the addition of biochar, using samples from the horizon A of Quartzeneics Neosols and 1% of biochar of cotton husks and sugarcane filtercake. The results showed that the fractionation of the soil in the particle size < 0.053 mm and between 0.053 to 2.0 mm, was an alternative to improve the accuracy of the determination of the distribution of soil particles by laser diffraction. The results of the particle selection parameters showed that there was a predominant sorting pattern ranging from poorly selected to very poorly selected (~95%). As for the kurtosis, there were predominance of very leptokurtics samples to extremely leptokurtics (~96%). The soils of different source materials presented alterations in the water retention capacity, and the smallest availability of water was found in the soils of the Botucatu Formation and the highest availability, in the soils of the jump formation of the clouds. The parameters of grain size, medium, sorting, asymmetry and kurtosis correlate significantly with the physico-hydro properties of the soil. The application of biochar in sandy soils has increased micropores and field capacity. Among the biochar studied, the biochar from cotton husks provided the highest increase in water availability.